The impact of entrepreneurship education on the entrepreneurial intention of students at the International University of Excellence in Mali: An exploratory study - Boubacar Sanogo; Oumar Bah; Amara Nimaga (The Journal of Entrepreneurial Finance (JEF), 2022)
This paper is research devoted to the self-employment of students of the International University of Excellence of Bamako through the teaching of entrepreneurship as a factor in the development of entrepreneurial intention among students in training. This choice is explained by several factors: the State's recruitment capacities in the public service are limited; the modern private sector which constitutes the natural outlet for young graduates is not in a position to offer employment for the many promotions of students trained annually who constitute thousands of people who increase the non-working population. It is becoming necessary to put in place systems that allow young graduates, especially those in training, to set up their own account through entrepreneurship. The practical study led us to consider the case of the International University of Excellence of Bamako. To study it, we focused our work on teaching entrepreneurship as a factor in the development of the entrepreneurial intention and self-employment of Students. As the parent population, we have a database of 236 students, from first to third year undergraduate students of the 2019 - 2021 academic years. This population is distributed between the different fields (Finance - accounting, Projects and organizations Management, Money - Finance - Banking and Insurance, Marketing-Communication, International Trade, Logistics - Transport, Business Intelligence). The information collected and processed will allow us to have a series of data on the possibilities offered by the teaching of entrepreneurship in terms of productivity of students of the International University of Excellence of Bamako before obtaining a university degree but also, to have an overview of self-employment and the teaching of entrepreneurship as a factor in the development of entrepreneurial intention and self-employment of the students of the International University of Excellence (IUE)
Keywords: 650; Self-employment; Education; Entrepreneurial Intent; Student; University